Implementation of Responsibility Accounting System Towards Cost Control and Cost Center Performance - Sri Trisnaningsih; Setyo Estiningrum (PT FORMOSA CENDEKIA GLOBAL, 2024)
Business competition requires companies to be able to look ahead and anticipate all possibilities that will affect thecompany's business development and hinder business development and growth. Responsibility accounting is a system that is structured in such a way as to suit the nature and activities of the company with the aim that each organizational unit can be accountable for the results of the activities of the units under its supervision. The aim of this research is to analyze in more depth the role and function of responsibility accounting as a tool for controlling and assessing cost center performance. The research method used in this research is using a literature review, especially articles published on Google Scholar. The articles listed are studied and analyzed in more depth using several keywords such as responsibility accounting, performance assessment, cost center and cost control. The results of this research conclude that the implementation of responsibility accounting greatly influences control and performance assessment in cost centers.Responsibility accounting will comprehensively measure and assess cost centers based on a comparison between budget targets and the actual budget that has been spent. By assessing the performance of cost centers, the company will be able to control and separate controllable costs from uncontrollable costs by each responsibility center, so that it can account forthe costs incurred by the company.